BUDAYA LITERASI DI KALANGAN WARGA MUHAMMADIYAH PADA PERIODE KEPEMIMPINAN HAEDAR NASHIR - Djaelani, M. Anwar; Munahar; Romelah; Nurhakim, Moh. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to: Assess the literacy activities performance among Muhammadiyah members, and explore opportunities to enhance literacy culture within the Muhammadiyah community based on experiences and initiatives across various regions. The significance of this research lies in the stagnant interest in reading in Indonesia, which has remained at 0.001 percent since 2006. Despite being an integral part of Indonesia, research data indicates a relatively low interest in reading among Muhammadiyah members. Paradoxically, the founders and many leaders of Muhammadiyah have shown exceptional literacy performance. This study employs a qualitative approach utilizing literature review methodology. Data sources and analysis materials are drawn from reliable scholarly literature and books. The findings suggest that, particularly within Muhammadiyah, there is optimism that literacy activities can be effectively maintained. Various strategies can be adopted for this purpose, such as organizing Literacy Training for its members.